INQUIRY-BASED SCIENCE COMIC PHYSICS SERIES INTEGRATED WITH CHARACTER EDUCATION (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
This study aimed to test the level of readability and feasibility of science comic, to knowcharacter development through a small test in some schools. The research design was Research Development, trials were using quasi-experimental pre-test-post-test experimental design. The instruments to measure attitudes were: a questionnaire and observation sheet, a test used to measure comprehension of the material. The results showed that learning science by inquiry-based science comic can improvecharacters and cognitive achievement of primary school students. Results in the form of inquiry-based science comic can be utilized in learning science as a companion teaching materials.